2018
DOI: 10.1186/s12884-018-1911-1
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and vomiting during pregnancy associated with lower incidence of preterm births: the Japan Environment and Children’s Study (JECS)

Abstract: BackgroundNausea and vomiting during pregnancy (NVP) is considered to be associated with favorable fetal outcomes, such as a decreased risk for spontaneous abortion. However, the relationship between NVP and preterm births remains unknown. This study was conducted to evaluate the association between NVP and the risk of preterm births.MethodsThe dataset of a birth cohort study, the Japan Environment and Children’s Study (JECS), was retrospectively reviewed. Participants’ experience of NVP prior to 12 gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
14
1
Order By: Relevance
“…Besides, some studies reported an association between NVP and increased risk of PTB [9,11], or LBW [9,11,14]. However, other studies reported lower risk of PTB [17,18], or LBW [19] in pregnant women who experienced NVP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, some studies reported an association between NVP and increased risk of PTB [9,11], or LBW [9,11,14]. However, other studies reported lower risk of PTB [17,18], or LBW [19] in pregnant women who experienced NVP.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that NVP is associated with adverse pregnancy outcomes, such as increased risk of preterm birth (PTB) [8][9][10][11], low birth weight (LBW) [8,9,[11][12][13][14], and neural tube defects [15,16]. While, some studies suggested that NVP has protective effects on pregnancy outcomes, such as lower risk of PTB [13,17,18], LBW [19], small for gestational age (SGA) [19], and pregnancy loss [20][21][22]. Still, no associations between NVP and PTB [19,23], LBW [18,23], or SGA [24] have been reported in other literatures.…”
Section: Introductionmentioning
confidence: 99%
“…Typical NVP occurs during the first trimester and is self-limiting, subsiding before 20 weeks of gestation [2]. It is considered to represent a healthy pregnancy, which has been linked to favorable obstetric and neonatal outcomes, including lower risk of miscarriage [3] and reduced odds for low birth weight and preterm birth [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that 33–83% of pregnant women experience nausea and vomiting of pregnancy (NVP) 1–4 . Other than nausea and vomiting, NVP also leads to loss of appetite and weight gain, affecting activities of daily living and sleep 5 .…”
Section: Introductionmentioning
confidence: 99%